Higher Bank Capital Requirements and Mortgage Pricing: Evidence from the Counter-Cyclical Capital Buffer - Basten, Christoph (Review of Finance, 2020)
Abstract We identify the effects of the Basel III macroprudential tool Counter-Cyclical Capital Buffer on mortgage lending. Using the first dataset on responses from multiple banks to each household, we find no evidence of explicit rationing. But as the CCyB applied only to mortgages, banks with higher mortgage specialization or lower capital cushions raise prices by an extra eight basis points. Bank level data then show that this allows them to slow their mortgage growth and rebuild capital cushions. While market-wide mortgage growth did not slow down significantly, the composition of mortgage suppliers thus moved to previously less exposed banks.